Glycine Exerts Renal Antioxidant Effects and Restores Hemodynamic Alterations in Rats Treated with Diclofenac Sodium: Roles of Renal Angiotensin Converting Enzyme, Angiotensin II Receptor and Mineralocortocoid Receptor (African Journal of Biomedical Research, 2023)
Diclofenac (DIC) is known to alter renal function in the form of hemodynamically-mediated acute renal failure. This study evaluated the protective role of the amino acid, glycine (Gly) on nephrotoxicity and acute hemodynamic alterations induced by DIC (9 mg/kg) in male Wistar rats. The rats were divided into four groups (n=7/group) including Group A (control); Group B (DIC-treated), Groups C (DIC + Gly1, 250 mg/kg) and Group D (DIC + Gly2 500 mg/kg). Systolic (SBP), diastolic (DBP) and mean arterial (MAP) blood pressures were significantly (p
Keywords: Kidneys; Diclofenac; Glycine; immunohistochemistry; receptors; blood pressure